1990
DOI: 10.1159/000235267
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition by Magnosalin and Magnoshinin, Compounds from ‘Shin-i’ (Flos magnoliae), of Adjuvant-Induced Angiogenesis and Granuloma Formation in the Mouse Pouch

Abstract: Inhibitory effects of magnosalin and magnoshinin, compounds from the crude drug ‘Shin-I’ (Flos magnoliae), on angiogenesis and pouch granuloma formation induced by an adjuvant containing croton oil were investigated. Magnosalin inhibited angiogenesis 2.4-fold (intra-pouch) and 9.7-fold (intraperitoneal) more strongly than granuloma formation. The inhibition of angiogenesis by magnosalin was 5-fold (intra-pouch) and 21-fold (intraperitoneal) weaker than that by hydrocortisone. In contrast, intraperitoneal magno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Of these lignans and neolignans, which are considered to be important bioactive ingredients, magnoshinin (35) and magnosalin (36) have been extensively studied. These two compounds have been reported to significantly inhibit croton oil-induced pouch granuloma formation and pouch exudation [36,74]. Kimura et al [74] suggested that inhibition of adjuvant-induced angiogenesis and granuloma formation by magnosalin (36) may be involved in the anti-inflammatory effects of FM.…”
Section: Bioactivities Of Components Of Flos Magnoliaementioning
confidence: 99%
See 1 more Smart Citation
“…Of these lignans and neolignans, which are considered to be important bioactive ingredients, magnoshinin (35) and magnosalin (36) have been extensively studied. These two compounds have been reported to significantly inhibit croton oil-induced pouch granuloma formation and pouch exudation [36,74]. Kimura et al [74] suggested that inhibition of adjuvant-induced angiogenesis and granuloma formation by magnosalin (36) may be involved in the anti-inflammatory effects of FM.…”
Section: Bioactivities Of Components Of Flos Magnoliaementioning
confidence: 99%
“…These two compounds have been reported to significantly inhibit croton oil-induced pouch granuloma formation and pouch exudation [36,74]. Kimura et al [74] suggested that inhibition of adjuvant-induced angiogenesis and granuloma formation by magnosalin (36) may be involved in the anti-inflammatory effects of FM. Magnosalin (36) and magnoshinin (35) have also been demonstrated to induce fetal bovine serum-stimulated and interleukin (IL-1 )-stimulated tube formations, which resulted in inhibition of endothelial cell proliferation [42,75].…”
Section: Bioactivities Of Components Of Flos Magnoliaementioning
confidence: 99%